Does a Small Body Have a Negative Impact on Minimally Invasive Mitral Valve Surgery? - Shirasaka, Tomonori; Kunioka, Shingo; Kikuchi, Yuta; Isikawa, Natsuya; Kanda, Hirotsugu; Kamiya, Hiroyuki (Frontiers in Surgery, 2022)
Backgrounds: Minimally invasive mitral valve surgery (MIMVS) in patients with a small body presents surgeons with a technically difficult surgical maneuver. We hypothesized that physique might negatively influence the safety and technical complexity of MIMVS. Methods: 121 patients underwent MIMVS in our institution between May 2014 and April 2020. These patients were categorized into two groups. The first group was the small physique group (n = 20) consisting of patients with a stature less than 150 cm. The second group was the normal physique group (n = 101) consisting of patients with a stature greater than 150 cm. The primary endpoint was freedom from death and major adverse cardiovascular and cerebrovascular events (MACCE). The secondary endpoint was freedom from moderate or severe mitral regurgitation. Results: Cardiopulmonary bypass time (130 ± 29 vs. 156 ± 55 min, p = 0.02) and aortic cross-clamp time (75 ± 27 vs. 95 ± 39 min, p = 0.03) were significantly shorter in the small physique group. Both in the early and midterm periods, there was no significant difference in the mortality (early, 5.0 vs.1.0 %, p=0.30. midterm, 5.0 vs. 1.0 %, p =0.20), MACCE (early, 5.0 vs. 6.9 %, p =0.65. midterm, 5.0 vs. 5.9 %, p = 0.87) and the residual MR (early, 0 vs. 1.0 %, p =0.66. midterm, 5.0 vs. 4.9 %, p = 0.91) between the two groups. Conclusions: Small physique is not a hurdle for MIMVS in terms of the safety of the operation.